Identifying, linking, and treating people who inject drugs and were recently infected with HIV in the context of a network-based intervention. Issue 11 (2nd November 2019) - Psichogiou, Mina; Giallouros, George; Pantavou, Katerina; Pavlitina, Eirini; Papadopoulou, Martha; Williams, Leslie D.; Hadjikou, Andria; Kakalou, Eleni; Skoutelis, Athanasios; Protopapas, Konstantinos; Antoniadou, Anastasia; Boulmetis, George; et al.
ABSTRACT: Identifying and linking people to care soon after HIV infection could limit viral transmission and protect their health. This work aims at describing the continuum of care among recently HIV-infected people who inject drugs (PWID) and participated in an intervention in the context of an HIV outbreak in Athens, Greece. The Transmission Reduction Intervention Project (TRIP) conducted risk network-based contact tracing and screened people for recent HIV infection. A comprehensive approach with a case management component that aimed to remove barriers to accessing care was adopted. Follow-up data on antiretroviral treatment (ART) and HIV-RNA levels were obtained from HIV clinics. TRIP enrolled 45 recently HIV-infected PWID (80% male) with a median viral load at recruitment of 5.43 log10 copies/mL. Of the recently infected persons in TRIP, 87% were linked to care; of these, 77% started ART; and of those on ART, 89% achieved viral load <200 copies/mL. TRIP and its public health allies managed to get most of the recently HIV-infected PWID who were identified by the program into care and many of them onto ART. This resulted in very low HIV-RNA levels. Treatment as prevention can work if individuals are aided in overcoming difficulties in entry to, or attrition from care. Trial registration: Uniform Trial Number identifier: NCT01827228.